Hadith #2338 - Sunan Abi Dawud - Khlf bin Hisham bin Th'lb خلف بن هشام بن ثعلب; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Raba'i bin Harash bin Jahsh ربعي بن حراش; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
Husayn ibn al-Harith al-Jadli from the tribe of Jadilah Qays said: The governor of Mecca delivered a speech and said: The Messenger of Allah (ﷺ) took a pledge from us that we should perform the rites of hajj after sighting the moon. If we do not sight it and two reliable persons bear witness, we should perform the rites of hajj on the basis of their witness. I then asked al-Husayn ibn al-Harith: Who was the governor of Mecca? He replied: I do not know. He then met me later on and told me: He w
Grade: Sahih

Hadith #3749 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Khlf bin Hisham bin Th'lb خلف بن هشام بن ثعلب; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Hospitality extend for three days, and what goes beyond that is sadaqah (charity).
Grade: Hasan

Hadith #4335 - Sunan Abi Dawud - Abu 'Ubaidah ibn al-Jarrah; al-'Ala' bin al-Msyb bin Rafa'i العلاء بن المسيب بن رافع; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; ibn Mas'ud; Khlf bin Hisham bin Th'lb خلف بن هشام بن ثعلب; Musa bin Nafi', Abu Shahab al-Hanat موسى بن نافع الأسدي أبو شهاب الحناط; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan Abi Dawud)
Do you think that his one of them, that is al-Mukhtar (al-Thaqaff)? He said : He is from the leaders.
Grade: Da'if